(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Literature and technology have made an effective intersection with each other since last few decades through the sociological and scientific discussion within the literature. The arrival of the globalization and industrial revolution make people’s higher interest upon various technological equipment’s which escalate the hybridity among literature and technology. The concepts of digital literature, social media platforms to escalate the independence of the writers and various digital supports to design, develop and ready to sell a book mostly influence on 21st century’s literature. The study has performed to discuss the entire hybridity and intersection of literature and technology in the digital era. A number of secondary qualitative data has collected in order to develop an empirical understanding on the topic. The information which has published onwards 2019 in English language has taken within the inclusion criteria in the inclusion criteria. Different peer reviewed sources and authentic sites provide textual assistance to develop the findings of the study. The study has found the use of technology in different sector of the civilization including literature has actually escalated the hybridity within the technology in 21st century’s digital era.